Factors associated with poor nutritional status among hemodialysis patients in Malaysia - Chan, Yoke Mun; Mohd Shariff, Zalilah; Lim, Christopher Thiam Seong; Goh, Bak Leong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Poor nutritional status is prevalent among hemodialysis patients, with limited studies available on how it is being influenced by other factors in the local context. The current study aimed to determine the nutritional status and its associated factors among hemodialysis patients. Methods: This was a study undertaken in a total of 455 hemodialysis patients (256 men and 199 women). The main outcome measure was Malnutrition Inflammation Score (MIS), which was utilized to identify nutritional and inflammatory status of the hemodialysis patients. Other evaluation tools included anthropometry and biochemical measurements as well as dietary assessment. Results: A high proportion of hemodialysis patients were malnourished (64.4%) and presented with inflammation (67.5%). Using multiple linear regression analysis, factors contributing to malnutrition were older age, lower lean body mass, higher interdialytic weight gain (IDWG), inadequate intakes of energy and protein, as well as presence of comorbidities and inflammation. Conclusion: The presence of malnutrition and inflammation were prevalent among hemodialysis patients. Several determinants of poor nutritional status of hemodialysis patients were modifiable and should be recognized while formulating and implementing appropriate intervention plans for this vulnerable group.